Konsep Dasar Strategi Pembelajaran Langsung (Direct Instruction) - Khoirun Nisah Lubis; Nurmala Sari; Gusmaneli Gusmaneli (Politeknik Kampar, 2024)
The purpose of this research is to determine the importance of direct learning strategies, their characteristics, types, application steps, as well as their advantages and disadvantages. The methodology of this research is a literature review. The findings of this study indicate that educators choose and apply direct learning strategies to convey knowledge to their students. This study focuses on several basic concepts in direct learning strategies that need to be known for their application in learning: the meaning of direct learning strategies, characteristics of direct learning strategies, types of direct learning strategies, steps for application, and the advantages and disadvantages of direct learning strategies.